Comparison of Nonlinear Grading Approaches for ZnSSe/GaAs (001) Heterostructrures. (24th April 2020) - Ayers, John E; Kujofsa, Tedi
Abstract : Compositional grading is commonly used to accommodate the lattice mismatch in metamorphic semiconductor device structures. Although linearly-graded or linear step-graded approaches are commonly used, there are experimental and theoretical grounds for the expectation that nonlinearly-graded buffer layers could offer advantages in the control of dislocations or strain. In this work we have conducted a detailed modeling study of nonlinearly-graded buffer layers in ZnSSe/GaAs (001) heterostructures to better understand the dislocation dynamics and defect behavior in such nonlinear buffers, and we make comparisons to the well-known case of linear grading.